A numerical study on aerodynamic wake flow control over airfoils by micro jet actuators. (2017) - Prawin, L.; Rose, J. Bruce Ralphin
The control of wake behind the aerodynamic surfaces plays an important role for increasing the efficiency of control surfaces. Among the numerous techniques use of micro jet actuator is superior because of its ability to fit under various flow conditions. The present article involves initially, the basic wind tunnel testing, to find the point of flow separation for the given airfoil model then The FLUENT analysis of a micro jet actuator with the use of moving wall boundary conditions for the bottom wall with dynamic mesh enabled mode is done. The airfoil with micro jet implanted system has been analysed for various free stream flow velocities. The results are obtained at different time steps ranging from 1 sec to 5 sec. Influence of micro jets on the boundary flow control has revealed striking information over the airfoil model at each time steps and the results are presented.